Study of potential energy at Sport Field Using PV Syst - Radiktyo Nindyo Sumarno; Dina Mariani (Politeknik Negeri Semarang, 2026)
Escalating global power consumption requires an urgent shift toward renewable energy technologies. This study analyzes the potential of a solar power plant (PLTS) at the Sport Field of Universitas Muhammadiyah Semarang. The researchers utilized PVsyst software to simulate an off-grid system design with a capacity of 12.65 kWp. The simulation evaluated five tilt angle variations ranging from 15o to 35o using Neosun 550 Wp modules. The analysis identifies the 15o tilt angle as the most optimal configuration. This specific setup generates 18.603 MWh of electrical energy annually. The system records maximum production in August and minimum production in January. The research confirms the feasibility of implementing this off-grid system to support facility operations.